Yield improvement by redundancy method for component calibration. Issue 13 (1st June 2013) - Enikeeva, F.; Morche, D.; Oguz, A.
Abstract : The benefits of a redundant channels methodology for the component calibration are explored. Proposed is a normal approximation of the yield in order to estimate the number of redundant components needed to provide a minimal area occupied by the components.